Obtenção e caracterização de compósitos nanoestruturados de poli(sulfeto de fenileno) reforçados com nanotubos de carbono - Ribeiro, Bruno [UNESP] (2015)
In this work, pristine and functionalized multiwalled carbon nanotubes reinforced poly (phenylene sulfide) composites were successfully obtained by melt mixing technique. The nanostructured composites were characterized by means of electrical, thermal, mechanical, rheological, and morphological methods. The electrical conductivity of neat PPS showed an increase by 11 and 9 orders of magnitude when 3.0 and 4.0 wt% of pristine MWCNT and functionalized MWCNT were incorporated in polymeric matrix, respectively. Moreover, the electrical percolation thresholds found on these systems were 2.1 and 3.6 wt%, suggesting the formation of three-dimensional conductive network within the polymeric matrix. The maximum crystallization temperature of PPS increased by about 19°C and 13°C due the incorporation of pristine (p-MWCNT) and functionalized filler (f- MWCNT), demonstrating the nucleating effect of the nanoparticles. Dynamic mechanical analysis showed an increase in storage modulus and glass transition temperature, due the incorporation of p-MWCNT and f-MWCNT in PPS matrix. However, it is worth to mention that the increment was bigger in p-MWCNT/PPS system. The maximum degradation temperature of PPS increased by about 14°C and 6°C due to the incorporation of 4,0 and 2,0 wt% of p-MWCNT and f-MWCNT, respectively, suggesting the formation of more thermally stable systems. The storage modulus (G’) of neat PPS presented an increase by 2 orders of magnitude when 2.0 and 3.0 wt% of pristine MWCNT and functionalized MWCNT were considered, with the formation of an interconnected nanotube structure, indicative of ‘pseudo-solid-like’ behavior. Percolation networks formed when the loading levels achieve up to 1.5 and 2.3 wt% for the composites with pristine MWCNT (p-MWCNT/PPS) and functionalized MWCNT (f-MWCNT/PPS), respectively. In addition, for ... (Complete abstract click electronic access below)